Phonological adaptation of lexical borrowings from Spanish in Norwegian - Krohn, Haakon S. (2020)
In this paper we carry out an analysis of the phonological adaptation of 76 lexical borrowings from Spanish in Norwegian. The adaptations are interpreted according to Kristoffersen’s (2000) generative description of the Norwegian phonological system. On the segmental level, a strong influence of the orthography is observed, which indicates that this factor should not be underestimated in studies of the same nature. However, there are also certain phoneme adaptations that can only be explained as a result of phonological or phonetic influence from Spanish. On the suprasegmental level, the position of the lexical stress in Spanish is retained in the majority of the borrowings, and almost all of them are assigned toneme 1, which manifests itself as the unmarked one.